Use of Call Balban Application in Assisting Motorcyclists - Melda Nurfadilah Rudiana; Levyna Cabytta Prasellina; Dimas Bagus Wiranatakusuma (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to develop a system that allows motorists to easily call a tire repair technician via an Android-based smartphone. The method used in compiling this research consists of data collection. analysis of user requirements, analysis of functional requirements and analysis of application system requirements. The tire patch application in this digital era provides a solution that helps motorists overcome the problem of flat or punctured tires. Suggestions that can be given to assist the development of tire patch location search applications for further development can be done by adding information on the location of tire patches that are open or closed both day and night and similar research can also be carried out with mobile-based applications.